2020
DOI: 10.4251/wjgo.v12.i6.632
|View full text |Cite
|
Sign up to set email alerts
|

Low ligation has a lower anastomotic leakage rate after rectal cancer surgery

Abstract: BACKGROUND For laparoscopic rectal cancer surgery, the inferior mesenteric artery (IMA) can be ligated at its origin from the aorta [high ligation (HL)] or distally to the origin of the left colic artery [low ligation (LL)]. Whether different ligation levels are related to different postoperative complications, operation time, and lymph node yield remains controversial. Therefore, we designed this study to determine the effects of different ligation levels in rectal cancer surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 40 publications
(42 reference statements)
1
34
0
1
Order By: Relevance
“…These studies involved a total of 4750 patients, with 1984 patients in the LL group and 2766 patients in the HL group. The baseline characteristics of the 14 eligible studies[ 4 , 5 , 7 , 13 - 23 ] are shown in Table 1 . Quality assessments of the included studies are shown in Table 2 and Figure 2 , and all endpoints are listed in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies involved a total of 4750 patients, with 1984 patients in the LL group and 2766 patients in the HL group. The baseline characteristics of the 14 eligible studies[ 4 , 5 , 7 , 13 - 23 ] are shown in Table 1 . Quality assessments of the included studies are shown in Table 2 and Figure 2 , and all endpoints are listed in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…No significant differences in urinary dysfunction (OR = 1.23, 95%CI: 0.95 to 1.59, P = 0.12; Figure 3A )[ 4 , 7 , 16 - 18 , 20 , 21 ] or urinary retention (OR = 1.51, 95%CI: 0.85 to 2.68, P = 0.16; Figure 3B )[ 5 , 14 , 22 , 23 ] were found between the LL and HL groups. The LL group did, however, have a lower risk of urinary infection (OR = 0.29, 95%CI: 0.16 to 0.54, P < 0.0001; 3C )[ 7 , 15 , 21 ] and a decreased risk of genitourinary dysfunction (OR = 0.32, 95%CI: 0.17 to 0.61, P = 0.0006; Figure 3D ), compared with the HL group[ 13 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 8 studies failed to provide su cient data and 11 studies published by non-Asian countries. Finally, 21 studies including 8 RCTs and 13 non-RCTs published between 2010 and 2020 were included in this systematic review and meta-analysis [4,7,9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. A total of 5947 patients (2519 patients in LL group and 3428 patients in HL group) were involved in the study.…”
Section: Description Of Study Selectionmentioning
confidence: 99%